Making Podcasts in the Collegiate French Writing Course. (28th January 2021) - Allen, Heather; Gamalinda, Sarah
Abstract : This study argues for grounding the teaching of presentational communication in a foreign language (FL) in Making- and Design-related concepts. We use the example of creating personal narrative podcasts in an advanced collegiate FL course to demonstrate how these concepts facilitate student learning outcomes in relation to genre awareness, digital literacy, and student engagement in presentational writing and speaking. A description is provided of the process of gaining understanding and carrying out thematic, generic, linguistic, and technical components of podcasting—a task that student self-reflections revealed as challenging yet ultimately rewarding.